CHALLENGES AND SOLUTIONS IN ENGLISH AND UZBEK TRANSLATIONS - Baxtiyorova Durdona Ixtiyorovna (Western European Studies, 2024)
The following article delves into the exploration of diverse translation hurdles encountered by language learners on a continual basis, aiming to offer solutions for addressing these critical issues within the translation process. Additionally, the primary objective of this paper is to illuminate the disparities between the English and Uzbek languages and how these distinctions may pose particular difficulties for translators
Keywords: idioms; articles; cultural difference.